Modeling and control of a three-phase T-type inverter - Zhang, Yuqiang (Nanyang Technological University, 2023)
Inverters are very important for energy transmission. How to construct a stable and controllable inverter with high power quality is a hot topic in current research. In this dissertation, the advantages of three-level(3L) inverters are compared with two-level(2L) inverters. Several different 3L inverters and the current research status of PWM are introduced in the dissertation. Specifically, the working state of the T-type inverter, the circulating current situation, switching loss and efficiency are analyzed.